Evaluation Report on First Years Working of Community Projects - Planning Commission (Planning Commission, 1954)
Scope of the Report.—The Programme Evaluation Organisation (P.E.O.) has been set. up for the purpose, among others, of keeping all concerned currently apprised of the progress of developmental plans in community project areas. the record of progress in terms of financial expenditure and of attainment of targets is normally prepared by the project administration in the "States and at the Centre. the P.E.O. report seeks to reveal the strong and weak points in the organisation and methods employed for the purpose of development. In addition to reports on all projects which are normally supplied by the State Governments to the Community Projects Administration (C.P.A.), the P.E.O. draws upon first-hand contacts with the working of developmental programmes in selected blocks in each State. As will be seen from Appendix I, which gives a fuller account of the organisation and working of the P.E.O., these blocks comprise community projects as well as pilot extension schemes. A variety of environmental and organisational conditions is found in these different centres. the P.E.O. report on progress is based on reports made by Development Commissioners and by the Evaluation Officers as well as on personal observations by the higher P.E.O. staff. This report seeks to convey an overall picture of the manner in which the developmental programme is proceeding. Its attempt is to underline general rather than local features. the report should, therefore, be treated as an appraisal of trends and not as an investigational report on particular projects which were chosen to represent the working of developmental programmes of different types in different conditions.
Evaluation Report
Government of India